The Effect of Human Resource Competency and Implementation of SIMDA on the Quality of Financial Statement at BPKAD Office of Gorontalo City - Ismet Sulila (Universitas Muhammadiyah Gorontalo, 2019)
This empirical study was intended to analyze, measure, and discuss the effect of human resource competency and the implementation of regional financial management information system on the quality of financial statement at BPKAD office of Gorontalo City.. Based on the initial study and research problem, hence the research used a quantitative approach and supported by ex post facto method. The technique of data analysis employed multiple regression. The findings of this study include: first, there has been a significant effect of human resource competency on the quality of financial statement at BPKAD office of Gorontalo City. Second, there has been an important effect of the Implementation of Regional Financial Management Information System on the quality of financial statement at BPKAD office of Gorontalo City. Third, there has been a contribution of the effect of human resource competency and Implementation of Regional Financial Management Information System simultaneously on the quality of financial statement at BPKAD office of Gorontalo City. Based on the previous conclusions, it is recommended: 1) To improve the human resource competency in regard of the use of regional financial management apps through training and advanced technical guidance activities, 2) To make an effective use of regional financial apps in various institutionsin Gorontalo City government, 3) that further research should examine the effect of other factors on the quality of financial statement.